Exopolysaccharide Produced by Probiotic Bacillus albus DM-15 Isolated From Ayurvedic Fermented Dasamoolarishta: Characterization, Antioxidant, and Anticancer Activities - Vinothkanna, Annadurai; Sathiyanarayanan, Ganesan; Rai, Amit Kumar; Mathivanan, Krishnamurthy; Saravanan, Kandasamy; Sudharsan, Kumaresan; Kalimuthu, Palanisamy; Ma, Yongkun; Sekar, Soundarapandian (Frontiers in Microbiology, 2022)
An exopolysaccharide (EPS) was purified from the probiotic bacterium Bacillus albus DM-15, isolated from the Indian Ayurvedic fermented traditional medicine Dasamoolarishta. Gas chromatography-mass spectrophotometry analysis revealed the heteropolymeric nature of the purified EPS with monosaccharide residues of glucose, galactose, xylose, and rhamnose. Size-exclusion chromatography shows that the molecular weight of the purified EPS is about 240 kDa. The nuclear magnetic resonance and X-ray powder diffraction analysis confirmed the carbohydrate polymer and non-crystalline amorphous nature of the purified EPS, respectively. The purified EPS showed the maximum flocculation and emulsification activity of 72.80 and 67.04%, respectively. The purified EPS also exhibits significant antioxidant activities on DPPH, ABTS, and nitric oxide radicals in a concentration-dependent way. Furthermore, the EPS had shown promising cytotoxic activity against the lung carcinoma cells (A549). These results indicate the promising nature of the EPS from strain B. albus DM-15 in food, cosmetic, pharmaceutical, and biomedical applications.